The Quality yearbook, 1997. - Cortada, James W.; Woods, John A. (New York McGraw-Hill, 1997)
Annual
Editors: James W. Cortada, John A. Woods.
Previous ed. entered under Cortada, James.
Keywords: Total quality management -- Periodicals